Means and methods of forming a positive attitude among students to physical exercises - Kozlova Galina Gennadievna; Khudieva Sabina Gilfanovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article shows the importance of forming a positive attitude towards physical culture among students, but by no means by force, but by educating their cognitive interest and convincing them of the need for physical exercises.